2005
DOI: 10.1021/bi050362p
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Environment Surrounding Iron−Sulfur Cluster 4 ofEscherichia coliDimethylsulfoxide Reductase

Abstract: Iron-sulfur ([Fe-S]) clusters are common in electron transfer proteins, and their midpoint potentials (E(m) values) play a major role in defining the rate at which electrons are shuttled. The E(m) values of [Fe-S] clusters are largely dependent on the protein environment as well as solvent accessibility. The electron transfer subunit (DmsB) of Escherichia coli dimethylsulfoxide reductase contains four [4Fe-4S] clusters (FS1-FS4) with E(m) values between -50 and -330 mV. We have constructed an in silico model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…Thus, the ET relay in E. coli fumarate reductase would favor electron transfer from FS3 to FS1. The effects of E m values in relation to electron transfer have also been previously examined in Me 2 SO reductase (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the ET relay in E. coli fumarate reductase would favor electron transfer from FS3 to FS1. The effects of E m values in relation to electron transfer have also been previously examined in Me 2 SO reductase (7).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylmethanesulfonyl fluoride was added to a final concentration of 0.2 mM, and cells were lysed using a French press. Membranes were prepared by differential centrifugation as previously described (7). Enriched membranes were prepared by centrifugation on a 55% sucrose cushion at 150,000 ϫ g for 90 min and were diluted to 25 ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSS301 was used for the growth experiments. TOPP2 was used for enzyme expression and spectroscopic studies, as we found that it was optimal for DmsABC overexpression and assembly (27). The plasmids (Table 1) used for cloning and expression included pBR322, pDMS160 (28), and pATZ (EcoRI-EcoRV fragment of pDMS160 (28) cloned into pTZ18R (Amp R lacZЈ (Pharmacia)) (laboratory collection)).…”
Section: Methodsmentioning
confidence: 99%
“…Cloning and Site-directed Mutagenesis-Construction of the site-directed mutants was carried out following the QuikChange method (Stratagene) (27) using pATZ as the template for mutagenesis. Mutants were verified by DNA sequencing carried out by the Department of Biochemistry DNA Core Facility at the University of Alberta.…”
Section: Methodsmentioning
confidence: 99%